Mixed load operation in current-powered mode complex shape - E. V. Ptitsyna; D. V. Ptitsyn; A. B. Kuvaldin (Омский научный вестник)
The article presents the results of experimental studies of energy, technological parameters of the load in a steady state after switching in the network by the example of a mixed load with a power supply current of a complex shape connected to a power supply unit (on a physical model of an electric furnace of resistance to indirect and direct heating with dark infrared emitters and energy-saving light sources, and low-voltage electrode water heater and energy-saving light sources). The purpose of the work is to study the electrical modes of mixed load in the power supply unit (electrotechnological and lighting systems) to develop recommendations for the selection of effective modes of mixed load operation when feeding with a complex form of current for the development of automated control systems. It is established that the mixed load with power supply by the current of complex form continues to work in the effective mode after switching in the network. To improve the efficiency of mixed load control, it is necessary to use two control channels: on the amplitude of the voltage (current) and on the frequency spectrum.